Screening of Arachis ssp. against Aspergillus flavus with in vitro seed colonization, EST-SSRs and generic primers and efficacy of different fungicidal control measures: SCREENING OF ARACHIS SSP. AGAINST ASPERGILLUS FLAVUS - KALYANI KUMARI; N SASIDHARAN (Journal of Oilseeds Research, 2018)
Aflatoxin produced in groundnut due to the infection by the fungus Aspergillus flavus is a major issue with respect to human health as well as export potential. Genetic resistance against this fungus is an important trait needed to counter the issue of Aflatoxin. In the present investigation, 50 Arachis subspecies genotypes including five different Arachis botanical types viz., spanish bunch, virginia bunch and valencia (cultivated) as well as two wild species viz., A. peruviana and A. aequatoriana were tested for their resistance to A. flavus. Compared to the reported resistant varietyICG1326 (J11), only three genotypes viz., ICG10933, ICG12625, TG26 showed resistance to fungal infection. Specific EST-SSR marker shown to be associated with resistance to A. flavus as well as generic molecular markers known to be associated with fungal resistance was tested in the selected genotypes. But, no strong association between markers and fungal resistance could be established. Also, among different fungicides tested for their ability to control A. flavus, carbendazim + thiram was found to be effective.